Lajja: A Critical Examination of Religious Fanaticism in Taslima Nasrin's Novel (Patan Prospective Journal, 2023)
Taslima Nasrin's novel, Lajja, explores the theme of religious fanaticism and its devastating impact on individuals and society. Published in 1993, the novel offers a poignant portrayal of a Hindu family living in Bangladesh and their struggles in the aftermath of the Babri Masjid demolition in India. This article aims to analyze Nasrin's Lajja in the context of religious fanaticism, examining the narrative's socio-political implications and its significance in promoting religious tolerance and understanding. The research paper follows both descriptive and analytical method, and is based on both primary and secondary sources. Taslima Nasrin’s Lajja served as the primary source while many articles and essays constituted the secondary sources.